Implementasi Good Corporate Governance dalam Meningkatkan Kinerja Karyawan di BSI KCP Pamekasan Jokotole - Sholihah, Aulia Fitriyatus; Handayani, Sri (JES (Jurnal Ekonomi Syariah), 2025)
Good Corporate Governance (GCG) is a corporate governance system designed to create added value for stakeholders through the implementation of fundamental principles such as transparency, accountability, responsibility, professionalism, and fairness. This study aims to explore the implementation of GCG at Bank Syariah Indonesia (BSI) KCP Pamekasan Jokotole and to analyze its impact on improving employee performance. The research employed a qualitative approach, with primary data collected through field observations, structured interviews, and documentation, while secondary data were obtained from relevant literature and institutional records. Data were analyzed using an interactive qualitative analysis technique, and data validity was ensured through source triangulation. The findings reveal that the implementation of GCG at BSI KCP Pamekasan Jokotole has produced a significant positive effect on employee performance. This improvement is evident in enhanced service quality, increased discipline, and higher levels of productivity among employees. Furthermore, the practice of GCG not only strengthens the company’s corporate value but also fosters greater trust from stakeholders, particularly customers and shareholders. The research highlights that effective governance practices create a professional, transparent, and harmonious work environment, which ultimately contributes to the sustainability and competitiveness of Islamic banking institutions in Indonesia.